Community Participation in Conserving The Existence of The Rejang Tribe Kejei Dance Through The Arts Community in Selupu Rejang Bengkulu - Bunga Naselia; Daryusti Daryusti (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2024)
This study analyzes (1) community participation in preserving the existence of the Kejei dance culture of the Rejang tribe through the arts community in Selupu Rejang District, Rejang Lebong Regency, Bengkulu Province. (2) factors that support and hinder community participation in preserving the Kejei dance culture of the Rejang tribe through the arts community in Selupu Rejang, Rejang Lebong, Bengkulu. This qualitative research involves collecting data using research observations, interview methods, and documentation. The interview technique was carried out in an unstructured manner using interview guidelines. Research data analysis is descriptive. The results of data processing in this study show that (1) efforts to preserve the Kejei dance of the Rejang tribe through the art community in Selupu Rejang district use three methods, namely: First, protection efforts are an effort to maintain the existence of the Kejei dance so that it does not become extinct by conducting dance training Kejei every week regularly. Second, development efforts are carried out through the quantity aspect of the dance, namely the development of the number of actors (dancers), the number of users, and the number of regions that receive the Kejei dance. Third, efforts to utilize the Kejei dance to introduce the Kejei dance to the broader community that the Kejei dance must be maintained. (2) factors supporting community participation in preserving the existence of the Kejei dance through the sanggar Tiang Bumei Selupu, namely social media that functions as a means of promotion, support from the government of Suban Ayam village and the government of Selupu Rejang district, a well-run studio management system, a strategic studio location, the enthusiasm of members of the sanggar Tiang Bumei Selupu and the support of all levels of society in Selupu Rejang district. The inhibiting factors for community participation in preserving the existence of the Kejei dance through the sanggar Tiang Bumei Selupu are limited infrastructure, funding problems, and the busyness of each member of the sanggar Tiang Bumei Selupu.